Utilization Of Turi Flour Growth Of Gurami (Osphronemus gouramy Lac) - Yuliani, Yuliani; Suharman, Indra; Adelina, Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe research was conducted at experimental pond, Fisheries and Marine Science Faculty Riau University fron January to March 2018. The aim of the research was to determine the benefits of the provision of turi leaves flour as a substitue soybean meal of Gurami (Osphronemus gouramy Lac). The experiment was design by completely random design and student duncan to differentiate among treatments. The treatments were applied namely ( 0, 25, 50, 75, and 100%). The result indicated that utilization of turi leaves flour does have significantly effect on grown of Gurami (Osphronemus gouramy Lac). The best result was achieved by treatment P3 ( 75% turi leaves flour and 25% soybean meal). Give an average feed dige stibility 62%, protein digestibility 78%, spesific growth rate 3,2%, feed efficiency of 43,22%, and protein retention 35,48% and survival rate of 95,00%. Water quality during the research are temperature 24-28 oc , Ph of 6-7, and disolved oxygen of 2,8-3,4 ppm. Keyword : Osphronemus gouramy Lac, turi leaves flour